Analysis Effectiveness of Jayamukti Farmer Card Program in Distributing Subsidized Fertilizers - Rifki Zulfadli; Sulistyo Sidik Purnomo; Kuswarini Sulandjari (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Purpose: This study aims to determine the effectiveness of the farmer card, analyze the efficiency of subsidized fertilizer distribution, and examine the relationship between the effectiveness of the farmer card usage and the subsidized fertilizer distribution. Methodology: The study uses both primary and secondary data. A simple random sampling method was employed to select 34 farmers with farmer cards in Jayamukti Village. Data analysis involved the Likert Scale, Validity Test, Reliability Test, Categorization Levels, and Spearman Rank Correlation Test. Results: The analysis shows that all data are valid and reliable. The effectiveness of the farmer card program falls into the high category (score 139). The effectiveness of subsidized fertilizer distribution also falls into the high category (score 135). Findings: The Spearman Rank Correlation Test revealed a significant relationship between the effectiveness of the farmer card program and the distribution of subsidized fertilizers, with a significance value of 0.005<0.05, indicating a significant correlation. Novelty: This research provides insights into the impact of the farmer card program on the efficiency of fertilizer distribution. Originality: The study offers a detailed analysis of the effectiveness of the farmer card program and its relationship to subsidized fertilizer distribution. Conclusions: The farmer card program effectively enhances the distribution of subsidized fertilizers, with a significant positive correlation between the program's effectiveness and fertilizer distribution efficiency. Type of Paper: Empirical Research Article